(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of this study is to determine the effect of using listening triangle and hot seating strategies on cognitive The aim of the current study is to identify the impact of using listening triangle and hot chair strategies on cognitive motivation in literature module among tenth-grade high school students. The researcher followed an experimental study including two experimental groups and a control group using a pre- and post-tests. 74 students were selected in Shahid Maa’mun Dabagh High School for Girls in the Centre of Erbil province for the academic year 2021-2022. The students were randomly selected to three groups in which 24 students for the first experimental group, 25 students for the second experimental group and of 25 students for the control group. The equalization of three groups is done by the researcher depending on the changing variables (age, intelligence, achievement level of students’ mothers, achievement level of students’ fathers, the previous year scores of students in Kurdish literature). The researcher used a questionnaire scale made by (Abdul Ridha and Badan, 2014), the questionnaire consists of (44) items, the answers to the items of the scale are (I strongly implement, I implement neutrally, I rarely implement, I do not implement). After giving the questionnaire to experts and taking their perspectives into consideration related to the appropriateness of the criterion, and finding the validity and reliability of the scale, the survey was distributed to the sample of 36 students before starting the experiment. The experimental study started on 14/10/2021 and ended on 7/12/2021. At the end of the experiment, the same scale was applied to the whole sample. After statistical analysis, the researcher concluded that both experimental groups were successful over the control group. In the light of the results, the researcher made some recommendations.